The impact of BRCA mutation and hormone receptor status on the outcomes of fertility preservation in breast cancer patients: a systematic review and meta-analysis - Ye, Liyu; Yang, Weihui; Guan, Huiyuan (Frontiers in Oncology, 2025)
BackgroundFertility preservation is a critical aspect of care for young breast cancer (BC) patients undergoing gonadotoxic treatments. BRCA mutation and hormone receptor (HR) status influence tumor biology and treatment outcomes. This study evaluated the impact of BRCA mutation and HR status on fertility preservation outcomes in BC patients.MethodsPubMed, Embase, Scopus, and Web of Science databases were searched for publications from inception to March 31, 2025 that report on fertility preservation outcomes stratified by BRCA mutation or HR status. Primary outcomes included the number of retrieved oocytes, maturation rates, and ovarian reserve indices such as anti-Müllerian hormone (AMH) levels and antral follicular count (AFC). Random-effects meta-analyses were performed.ResultsThirteen studies involving approximately 1,654 participants were included in the meta-analysis. Patients with no BRCA mutations reported significantly higher mature oocytes (MD: -1.48, 95% CI: -2.63 to -0.34) compared to those with BRCA mutations and non-significant total oocyte yield (MD: -1.37, 95% CI: -3.13 to 0.40). AFC and AMH levels showed no significant intergroup differences. Additionally, estrogen receptor (ER)-positive patients exhibited better ovarian response, with higher AFC (MD: 1.37, 95% CI: 0.48 to 2.26) and greater oocyte yield (MD: 1.35, 95% CI: 0.67 to 2.02).ConclusionOur results show that BRCA mutations may be associated with significantly diminished mature oocyte production during fertility preservation in BC patients. On the contrary, ER-positive status seems to be associated with high AFC and oocyte yield indicating a more advantageous ovarian response. The present findings are from a limited number of heterogenous studies and hence must be interpreted with caution.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025641361.